Armenia : Growth Challenges and Government Policies, Volume 2. Main Report - World Bank (Washington, DC, 2013)
This report reviews growth trends in Armenia for the period 1994-2000, outlines major weaknesses of existing development patterns, and suggests a package of policy recommendations designed to accelerate enterprise restructuring, attract investment, and encourage the creation of new businesses in the medium term (three to five years). Such steps are needed to systain (and preferably to increase) the current growth rates, to stop emigration among the young and skilled, and to reduce poverty. The government needs to focus much more clearly on generating the environment for private sector led growth by removing bottlenecks in policies, infrastructure, and institutions that prevent new private businesses from flourishing. International aid donors can help by supporting the removal of administrative barriers for investments, the rehabilitation of infrastructure, and the creation of "restructuring agencies" that will enable firms in key sectors to overcome or avoid common constraints to business growth in Armenia. Successful restructuring by such firms should have a demonstration effect on the country's economy and help consolidate public support for moving forward the program of reform begun a decade ago.